Estudo farmacológico do Cymbogon citratus (D.C.) STAPF - Ferreira, Maria do Socorro Cordeiro (1984)
A pharmacological study of. Cymbopogon citratus has been made studying its essencial oil, hydrolate and citral, the last compound beeing a pure component of the oil. These drugs promoted a spasmolitic effect on gut smooth muscle, proprably inespecific in nature. A previous pharmacological screening demonstrated that the tree substances are devoided of effects on cardiac and striated muscle, as well as on arterial blood pressure and on dog diuresis. The LD5O of the essencial oil in mice was 0,7ml, as determined by the method of Tainter and Miller. The studies were conducted mainly on duodenum of the rabbit, uterine preparation of the rat pretreated by estrogens and guinea pig ileum. In all the preparations , hydrolate or pseudohydrolate and citral blocked the spasms produced by Ace- tilcholine or barium chloride and inhibited the pepdular move- ment spontaneously observed in rabbit duodenum. A more detailed study was conducted in isolated guinea pig ileum, to study the blockade of citral towards other mediai tors such as histamine, serotonin, bradikynin and Acetilcholi-ne; under this treatment citral promoted a blocked of the ago- nist effects produced by these drugs.